2015
DOI: 10.1002/2014gb005075
|View full text |Cite
|
Sign up to set email alerts
|

Transports and budgets of anthropogenic CO2 in the tropical North Atlantic in 1992–1993 and 2010–2011

Abstract: The meridional transport of anthropogenic CO 2 (C ant ) in the tropical North Atlantic (TNA) is investigated using data from transoceanic sections along 7.5°N and 24.5°N, carried out in the early 1990s and 2010s. The net C ant transport across both sections is northward. At 7.5°N, this transport increased from 315 ± 47 kmol s À1 in 1993 to 493 ± 51 kmol s À1 in 2010; similarly, across 24.5°N it grew from 530 ± 46 kmol s À1 in 1992 to 662 ± 49 kmol s À1 in 2011. These changes result from modifications in the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 43 publications
1
21
0
Order By: Relevance
“…Surprisingly, their estimates of natural air‐sea CO 2 flux are in agreement with ours. Therefore, we suspect that for this specific region, the ocean inverse methods present deficiencies in the estimation of the divergence/convergence of DIC forms, in agreement with Pérez et al [], likely due to an improper representation of the ocean circulation [ Zunino et al , ]. While the ocean inversion methods are tremendously important for covering areas where in situ data are not available, the analysis of budgets of DIC (natural, anthropogenic, and contemporary) using only in situ data are needed to provide benchmarks for validation of ocean inversion methods as well as for specifying constraints at regional scale.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Surprisingly, their estimates of natural air‐sea CO 2 flux are in agreement with ours. Therefore, we suspect that for this specific region, the ocean inverse methods present deficiencies in the estimation of the divergence/convergence of DIC forms, in agreement with Pérez et al [], likely due to an improper representation of the ocean circulation [ Zunino et al , ]. While the ocean inversion methods are tremendously important for covering areas where in situ data are not available, the analysis of budgets of DIC (natural, anthropogenic, and contemporary) using only in situ data are needed to provide benchmarks for validation of ocean inversion methods as well as for specifying constraints at regional scale.…”
Section: Discussionmentioning
confidence: 99%
“…The ocean inversion methods combine DIC observations with transport and mixing from ocean models, assuming no sources or sinks in the ocean interior, allowing them to infer the air‐sea fluxes for different regions of the ocean from the imbalance of the lateral advection [ Mikaloff Fletcher et al , , ; Gruber et al , ]. Nevertheless, some works, based on in situ estimates of the ocean circulation, have suggested that the lateral advection of C ant is underestimated by ocean inverse models [ Pérez et al , ; Zunino et al , ]. So, if this is also true for DIC, we suspect that the air‐sea fluxes inferred from ocean inverse methods may be biased.…”
Section: Introductionmentioning
confidence: 99%
“…From 1989 to 1995 the NAO was in a high positive phase, followed by a negative phase starting in 2002 [ Pérez et al ., ], after a minimum in 2010 the NAO has been rapidly increasing (see https://climatedataguide.ucar.edu/climate-data/hurrell-north-atlantic-oscillation-nao-index-pc-based). Recent studies showing large annual and decadal variation in the strength of the Atlantic meridional overturning circulation which can vary by 30% annually [ Srokosz and Bryden , ] could also contribute to decadal variations in carbon uptake, particularly in the tropical North Atlantic [ Pérez et al ., ; Zunino et al ., ].…”
Section: Estimating δCanthro Inventory Change In the Atlanticmentioning
confidence: 99%
“…A slowdown of the MOC would result in a decrease in the ability of the North Atlantic to transport CO 2 from the atmosphere into the interior ocean, but available data have been insufficient to confirm this [ Sabine and Tanhua , ]. Recent work has also demonstrated a strong relationship between the North Atlantic Oscillation (NAO) and uptake rates in the Atlantic [ Pérez et al ., , ] as well as large variability in the anthropogenic CO 2 sink in the tropical North Atlantic [ Zunino et al ., ], indicating that strong decadal variability in the North Atlantic carbon sink. Wanninkhof et al .…”
Section: Introductionmentioning
confidence: 99%
“…The deep convection processes there behave as a driving mechanism for the Meridional Overturning Circulation (Kuhlbrodt et al, 2007;Rhein et al, 2011;Sarafanov et al, 2012), which transports heat to high latitudes in the North Atlantic and is predicted to slow down at the end of the present century (IPCC, 2007). Additionally, the SPNA presents the highest anthropogenic CO 2 storage rate of all oceans (Khatiwala et al, 2013) due to both the advection of surface waters enriched with anthropogenic CO 2 in the subtropical North Atlantic (Pérez et al, 2013;Zunino et al, 2015) and their deep injection in the subpolar gyre (Pérez et al, 2010). In addition, the SPNA is one of the few oceanic regions where significant cooling was detected over 1955-2010 while the rest of the world oceans were warming (Levitus et al, 2012).…”
Section: Introductionmentioning
confidence: 99%